Histopathological study of ovarian lesions at a tertiary health-care center - Paritosh Shringi,; Matariswa Samanta,; Vishakha Behl,; Pawan Nikhra,; Chandra Mathur,; Kavita Gupta, (Asian Journal of Medical Sciences, 2023)
Background: Ovary is the most common site of non-neoplastic and neoplastic lesions, can appear at any age, and is the leading cause of hospitalization and surgery. The ovary is made up of totipotent sex cells and multipotent mesenchymal cells. As a result, when it becomes neoplastic, almost any type of tumor can develop. Aims and Objectives: The aim of the study was to find out the histopathological findings of ovarian lesions. Materials and Methods: The present study was carried out in the Department of Pathology, Pacific Institute of Medical Sciences, Udaipur, from April 2021 to September 2022 and includes 102 cases of ovarian lesions. Histopathology department received the specimens in formalin filled container and performed routine grossing and H and E staining procedure. Results: The incidence of neoplastic ovarian lesion was 40.2%. Majority of non-neoplastic lesion of ovary was follicular cyst (42.6%) followed by simple cyst (36.1%). Surface epithelial tumor was diagnosed in majority of ovarian tumors (73.2%) followed by germ cell tumor (22.0%). The majority histopathological benign tumor type was serous cystadenoma (43.9%) and malignant was high-grade serous carcinoma (14.63%). Conclusion: The incidence rate increased with age, with the greatest number of new cases being diagnosed beyond 4th and 5th decade. In our study, the youngest patient was of 2 year and oldest was of more than 60 years. However, histopathological study of ovarian tumors is still considered as a gold standard method, our observations and results proved to be valuable base line information regarding frequency and pattern of ovarian tumors.